Prevalence of pretreatment HIV drug resistance in Cameroon following a nationally representative WHO survey. (19th June 2018) - Tchouwa, Gaëlle F; Eymard-Duvernay, Sabrina; Cournil, Amandine; Lamare, Nadine; Serrano, Laetitia; Butel, Christelle; Bertagnolio, Silvia; Mpoudi-Ngole, Eitel; Raizes, Elliot; Aghokeng, Avelin F; ,
Abstract: Background: Pretreatment HIV drug resistance (PDR) has the potential to affect treatment outcome and mortality. We present here the first nationally representative PDR study conducted in Cameroon. Methods: From February to July 2015, HIV-infected ART initiators were recruited from 24 randomly selected clinics situated in both urban and rural regions. Dried blood spot specimens were collected from study participants at these clinics and centralized in a reference laboratory in Yaoundé, Cameroon, for drug resistance testing. HIV drug resistance mutations were identified using the Stanford algorithm. Results: Overall, from the 379 participants recruited, 321 pol sequences were successfully interpreted. Two hundred and five sequences were from patients attending urban ART clinics and 116 from patients seen at rural facilities. Nine percent of sequences (29/321) were from participants reporting previous exposure to antiretrovirals. PDR prevalence among all initiators was 10.4% (95% CI 5.4%–19.1%), with 14.2% (95% CI 6.6%–27.9%) reported in urban areas and 4.3% (95% CI 1.2%–14.3%) in rural areas. Among participants with no prior exposure to antiretrovirals, PDR prevalence was 10.4% (95% CI 4.7%–21.5%) overall, with 13.5% (95% CI 5.1%–31.5%) and 5.3% (95% CI 1.4%–17.5%) reported in urban and rural areas, respectively. Conclusions: Our findings indicate that at least 10% of patients initiating ART in Cameroon carry viruses with PDR and may be at risk of premature ART failure. The high level of NNRTI-associated resistance is of particular concern and supports introduction of drugs with a higher genetic barrier to resistance.